Configuration compression for FPGA-based embedded systems. - Dandalis, A. (IEEE Transactions on VLSI systems)
Field programmable gate arrays (FPGAs) are a promising technology for developing high-performance embedded systems. The density and performance of FPGAs have drastically improved over the past few years. Consequently, the size of the configuration bit-streams has also increased considerably. As a result, the cost-effectiveness of FPGA-based embedded systems is significantly affected by the memory required for storing various FPGA configurations. This paper proposes a novel compression technique that reduces the memory required for storing FPGA configurations and results in high decompression efficiency. Decompression efficiency corresponds to the decompression hardware cost as well as the decompression rate. The proposed technique is applicable to any SRAM-based FPGA device since configuration bit-streams are processed as raw data. The required decompression hardware is simple and the decompression rate scales with the speed of the memory used for storing the configuration bit-streams. Moreover, the time to configure the device is not affected by our compression technique. Using our technique, we demonstrate up to 41% savings in memory for configuration bit-streams of several real-world applications.